Neuroprotective effect of myoinositol on the cellular model of glutamate stress as a basis for the prevention of disorders of intrauterine development of the brain - A. G. Kalacheva; I. Yu. Torshin; E. V. Stelmashuk; E. E. Genrikhs; O. P. Alexandrova; L. G. Khaspekov; O. A. Gromova (Фармакокинетика и Фармакодинамика)
Myoinositol is the basis for the synthesis of an important group of signal molecules, inositolphosphates, which mediate signal transmission from receptors of growth factors and neurotransmitters. Grants myo-Inositol promote the prevention of folate-resistant defects and neuroprotection of the fetal brain ischemia. The paper presents the results of a study of the effects of myoinositol on the growth of cerebellar neurons in culture under glutamate stress. It is shown that the effects of myoinositol on the survival of neurons (+17 %) exceed the effects of drugs that are usually used for neuroprotection (peptide extracts - + 10 %, choline preparations - no more than 3 %). Confirmed in the present work, a direct neuroprotective effect of myo-Inositol indicates the importance of the use of myo-Inositol during pregnancy with the aim of neuroprotection of the fetal brain.